The Evolving Role of Next-Generation Sequencing in Screening and Diagnosis of Hemoglobinopathies - Achour, Ahlem; Koopmann, Tamara T.; Baas, Frank; Harteveld, Cornelis L. (Frontiers in Physiology, 2021)
During the last few years, next generation sequencing has undergone a rapid transition from a research setting to clinical application becoming the method of choice in many clinical genetics laboratories for the detection of disease causing variants in a variety of genetic diseases involving multiple genes. The hemoglobinopathies are the most frequently found Mendelian inherited monogenic disease worldwide and comprise a complex group of disorders frequently involving the inheritance of more than one abnormal gene. The aim of this review is to present the role of NGS in both screening and pre- and postnatal diagnostics of the hemoglobinopathies and the added value of NGS is discussed based on the results described in the literature. Overall, NGS has added value in large scale high throughput carrier screening and in the complex cases for which common molecular techniques have some inadequacies. It is proven that the majority of thalassemia cases and Hb variants can be diagnosed using routine analysis involving a combined approach of hematology, hemoglobin separation and classical DNA methods, however, we conclude that Next Generation Sequencing can be a useful addition to the existing methods in the diagnosis of these disorders.